KONSEP TAWAKAL DALAM KAJIAN AKHLAK TASAWUF BERDASARKAN DALIL PADA AL QUR’AN - Anri Naldi; Cahaya Cahaya; Muhammad Zein Damanik (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
For every Muslim, tawakal is one of the characteristics that must be possessed. Tawakal is a great character of faith. According to Muhammad bin Hasan asy-Sharif, tawakal is a person who knows that only Allah is responsible for his sustenance and affairs. Therefore, he relies solely on Him and does not put his trust in other than Him. may be harmful and may not be of any benefit. According to al-Imam Ahmad, tawakal is a deed of the heart, because it is a deed of the heart, so it is not expressed in verbal words and the deeds of the body. Sahl said that tawakal is submission to Allah according to whatever He wills. Whereas Dzun-Nun said that trustworthiness means not relying on self-regulation, apart from one's own power and strength, the trustworthiness of a servant becomes stronger if he knows that Allah is watching and watching him. Because of this, tawaqal is something that every Muslim must have and know. Tawakal is the basic thing, but it will be strengthened by the arguments that will guide the tawakal.